Pentingnya Pemahaman Eskatologi Menurut Matius 24 bagi Jemaat GPdI Pisga - Dolfinus B. Watopa; Zulkisar Pardede (Sekolah Tinggi Teologi Torsina Surakarta, 2020)
Eschatology is generally understood as the teaching of the Bible about the last days or the time before Jesus' return. The assurance of Christ's second coming, accompanied by the events of the resurrection and the final judgment, is one of the doctrinal points that many theologians agree on. This is also one of the important doctrines in the GPdI. This article aims to show the importance of this doctrine being taught and understood in the church, especially in the GPdI Pisga Waropen Timur environment. The method used in this research is the interpretive descriptive analysis method of the Bible text in Matthew 24. In conclusion, the GPdI Pisga Waropen Timur congregation has a good understanding of the concept and a good understanding of Matthew 24's eschatology.AbstrakEskatologi umumnya dipahami sebagai pengajaran Alkitab mengenai hari-hari terakhir atau masa menjelang Yesus datang kembali. Kepastian keda-tangan Kristus kedua kalinya yang disertai dengan peristiwa kebangkitan dan penghakiman terakhir, merupakan salah satu pokok doktrinal yang disetujui oleh banyak ahli teologi. Hal ini juga menjadi salah satu doktrin penting dalam GPdI. Artikel ini bertujuan untuk memperlihatkan pentingnya doktrin ini diajarkan dan dipahami di gereja, terutama di lingkungan GPdI Pisga Waropen Timur. Metode yang digunakan dalam penelitian ini adalah metode analisis deskriptif interpretatif terhadap teks Alkitab pada Matius 24. Kesimpulannya, jemaat GPdI Pisga Waropen Timur memiliki pemahaman yang baik tentang konsep dan pemahaman yang baik tentang eskatologi Matius 24.